2015
DOI: 10.1002/cctc.201501056
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Co3O4 Nanocatalysts with Different Dimensional Architectures on Methane Combustion

Abstract: We fabricated Co 3 O 4 catalysts with different spatial structures, such as zero-dimensional (nanoparticles), one-dimensional (nanorods), two-dimensional (nanoplates), and three-dimensional (mesoporous and microporous) structures, for methane combustion. The Co 3 O 4 catalysts with different dimensional architectures demonstrated different activitiesf or the breaking of the CÀHb ond of methane. In particular, Co 3 O 4 with 2D structure gave rise to the highest activity amonga ll the samples, in which methanec … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…6a), the peaks at the binding energy of 779.9, 781.5 and 785.5 eV are related to surface Co 3+ , Co 2+ and satellite peak of Co species, respectively. 17,18,31 In addition, the Mn 2p 3/2 XPS spectrum in Fig. 6b , represents an oxygen vacancy in the catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6a), the peaks at the binding energy of 779.9, 781.5 and 785.5 eV are related to surface Co 3+ , Co 2+ and satellite peak of Co species, respectively. 17,18,31 In addition, the Mn 2p 3/2 XPS spectrum in Fig. 6b , represents an oxygen vacancy in the catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Various transition metal oxides as active components in reaction processes have been extensively studied to replace noble metals over the past several years, because they have low cost, unique structural morphology, adequate catalytic activity and high thermal stability. 3,[17][18][19][20][21] Co 3 O 4 , a transition metal oxide, has been proven to excellent catalytic activity in numerous reactions duo to its superior physical-chemical properties. [22][23][24][25][26][27] Additionally, extensive efforts have revealed that the synergistic effect of Co species and other transition metal oxides has dramatically enhanced the redox properties and catalytic activities due to the formation of a solid solution, compared with single oxides.…”
Section: Introductionmentioning
confidence: 99%
“…As suggested in several studies, during methane combustion the lattice oxygen in the oxide surface contributes to the oxidation of CH x , thus leading to the formation of an oxygen vacancy, available for oxygen adsorption from the gas-phase. Both the adsorbed oxygen, as well as the surface lattice oxygen, are considered crucial for oxidation reactions, as they contribute to the adsorption/activation of oxygen and, thus, the desired oxidation of intermediates on the catalyst surface [11,32,33]. Oxygen-temperature programmed desorption (O 2 -TPD) experiments have evidenced that oxygen molecules were released from Co 3 O 4 nanomaterials, suggesting that these oxygen molecules were adsorbed on the surface oxygen vacancies of the oxides [32].…”
Section: H 2 -Tpr and O 2 -Tpd Studiesmentioning
confidence: 99%
“…Among these, Co 3 O 4 exhibits good activity for methane combustion attributed to a spinel‐type structure with variable Co oxidation states and a high density of oxygen vacancies on the surface . Additionally, the specific exposed facets and morphology of Co 3 O 4 plays an important role in the catalysis . Materials with exposed (110) planes show enhanced catalytic activity for methane oxidation compared with those only exposing (100) or (111) facets, enabling complete methane conversion below 400 °C (GHSV = 40 000 mL g −1 h −1 ) .…”
Section: Introductionmentioning
confidence: 99%